Intestinal Microbiota Confer Protection by Priming the Immune System of Red Palm Weevil Rhynchophorus ferrugineus Olivier (Coleoptera: Dryophthoridae) - Muhammad, Abrar; Habineza, Prosper; Ji, Tianliang; Hou, Youming; Shi, Zhanghong (Frontiers in Physiology, 2019)
The immune system of animals, including insects, is the vital factor to maintain the symbiotic interactions between animals and their associated microbes. However, the effects of gut microbiota on insect immunity remain mostly elusive. Red palm weevil (RPW), Rhynchophorus ferrugineus Olivier, is a destructive pest of palm trees worldwide, which has forged alliances with its gut microbiota. Here, we found that the aposymbiotic insects succumbed at a significantly faster rate than conventionally reared (CR) ones upon bacterial infection. Physiological assays confirmed that CR insects had stronger antimicrobial activity and higher phenoloxidase activity in contrast to germfree (GF) ones, indicating that the systemic immune responses of GF individuals were compromised markedly. Interestingly, under the bacterial challenge conditions, the reassociation of gut microbiota with GF insects could enhance their survival rate by rescuing their immunocompetence. Furthermore, comparative transcriptome analysis uncovered that 35 immune-related genes, including pathogen recognition receptors, effectors and immune signaling pathway, were significantly downregulated in GF insects as compared to CR ones. Collectively, our findings corrobate that intestinal commensal bacteria have profound immunostimulatory effects on RPW larvae. Therefore, knowledge on the effects of gut microbiota on RPW immune defenses may contribute to of set up efficient control strategies of this pest.